Trade Flows, Private Credit and the Covid-19-Pandemic: Panel Evidence from 35 OECD Countries - Guglielmo Maria Caporale; Anamaria Sova; Robert Sova (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the impact of the Covid-19 pandemic on exports and imports in the case of 35 OECD countries during the 2019Q1-2021Q2 period using a dynamic panel approach, specifically the system Generalized Method of Moments (GMM). In contrast to earlier studies, the empirical specification incorporates not only an index for the restrictive (and fiscal) measures adopted by national governments, but also an interaction term with private credit which captures the role of the financial sector in the context of the current crisis. The findings suggest that the negative effects of the Covid-19 pandemic on international trade can be attenuated through (policies supporting) private credit, which confirms the importance of the trade-finance nexus.
Keywords: C25; E61; F13; F15; 330; Covid-19 pandemic; stringency index; overall government response index; credit to the private non-financial sector; dynamic panel models; GMM